Thermal fluid dynamics of liquid bridge transfer in laser wire deposition 3D printing. (4th July 2019) - Hu, Renzhi; Luo, Manlelan; Liu, Tongtong; Liang, Lvjie; Huang, Anguo; Trushnikov, Dmitry; Karunakaran, K. P.; Pang, Shengyong
ABSTRACT: Liquid bridge transfer mode is most favourable deposition pattern in laser wire deposition. However, the thermal fluid dynamics has not been well understood. In this paper, we systematically investigated the fluid dynamics during liquid bridge transfer in the printing process. We developed a novel three-dimensional heat transfer and fluid flow model by considering the effect of wire feeding. The results showed that for typical process parameters the Weber number ( We ) of the fluid on the liquid bridge is on the order of O(10 0 ∼10 1 ). A dimensionless slenderness number ( Sl ), was roughly estimated at the range of 3.17∼4.57 for maintaining the liquid bridge. This study provides the fluid mechanics insights of the metal transfer mechanisms in 3D printing process.